Women's perceptions of antenatal, delivery, and postpartum services in rural Tanzania - Gladys Reuben Mahiti; Dickson Ally Mkoka; Angwara Dennis Kiwara; Columba Kokusiima Mbekenga; Anna-Karin Hurtig; Isabel Goicolea (Taylor & Francis Group, 2015)
Background: Maternal health care provision remains a major challenge in developing countries. There is agreement that the provision of quality clinical services is essential if high rates of maternal death are to be reduced. However, despite efforts to improve access to these services, a high number of women in Tanzania do not access them. The aim of this study is to explore women's views about the maternal health services (pregnancy, delivery, and postpartum period) that they received at health facilities in order to identify gaps in service provision that may lead to low-quality maternal care and increased risks associated with maternal morbidity and mortality in rural Tanzania. Design: We gathered qualitative data from 15 focus group discussions with women attending a health facility after child birth and transcribed it verbatim. Qualitative content analysis was used for analysis. Results: 'Three categories emerged that reflected women's perceptions of maternal health care services: "mothers perceive that maternal health services are beneficial," "barriers to accessing maternal health services" such as availability and use of traditional birth attendants (TBAs) and the long distances between some villages, and "ambivalence regarding the quality of maternal health services" reflecting that women had both positive and negative perceptions in relation to quality of health care services offered'. Conclusions: Mothers perceived that maternal health care services are beneficial during pregnancy and delivery, but their awareness of postpartum complications and the role of medical services during that stage were poor. The study revealed an ambivalence regarding the perceived quality of health care services offered, partly due to shortages of material resources. Barriers to accessing maternal health care services, such as the cost of transport and the use of TBAs, were also shown. These findings call for improvement on the services provided. Improvements should address, accessibility of services, professionals' attitudes and stronger promotion of the importance of postpartum check-ups, both among health care professionals and women.